Stroke in sickle cell patients, epidemiology, pathophysiology, systemic and surgical treatment options and prevention strategies - Siddharth Shah; Amelia H. Alberts; Tran B. Ngo; Brandon Lucke‐Wold (Wiley, 2024)
Abstract Background A hereditary haemoglobinopathy known as sickle cell disease (SCD) affects over 100 000 people in the United States severely. Cerebrovascular disease is a prominent consequence of SCD. By the age of 30, 53% of patients have silent cerebral infarcts (SCIs) (a stroke that occurs without any obvious symptoms because it damages a small part of the brain that isn't responsible for any essential functions), and by the age of 40, 3.8% have overt strokes. Main body The multidimensional burden of cerebrovascular illness in SCD is reviewed in detail in this article, which includes both clinical strokes and the frequently asymptomatic SCIs. The intricate pathophysiology of SCD and stroke is explored. With SCD, there are currently very few methods for preventing primary and secondary stroke; the most common ones are hydroxyurea and blood transfusion. Nevertheless, not enough research has been done on the possible contributions of anticoagulation and aspirin to strokes linked to SCD. Promising evidence is also highlighted in the study, suggesting that new drugs intended to treat SCD may be able to alleviate leg ulcers and renal impairment in addition to reducing unusually high transcranial Doppler flow velocity - a crucial component of cerebrovascular events. Given that these novel medications specifically target haemolysis and vaso‐occlusion, the two main causes of strokes in this population, more research is desperately needed to determine whether they are effective in avoiding strokes in people with SCD. The literature review also emphasizes how common healthcare inequities are and how they hinder advancements in SCD research and management in the United States. Conclusion To successfully address these inequities, the evaluation recommends more funding for both SCD management and research, as well as for patient and clinician education. This multimodal viewpoint highlights the intricate terrain of cerebrovascular problems associated with SCD and the urgent need for all‐encompassing and fair strategies to improve patient outcomes and advance research.